NEOADJUVANT DIAGNOSIS AND MANAGEMENT OF CHRONIC ENDOMETRITIS - V. A. KRUTOVA; A. M. CHULKOVA; D. L. VANYAN; L. M. CHUPRINENKO; R. A. KASPARYAN; E. E. KOPYTKO; T. G. DYAKOVA (Кубанский научный медицинский вестник, 2018)
Aim. The purpose of this research was informational content assessment of the anamnestic data in diagnosing of chronic endometritis before its histologic confirmation and possibility of the timely beginning of complex therapy of pathology.Materials and methods. To achieve the aim of the retrospective analysis of 303 case reports of patients who underwent endometrium papel biopsy as a part of examination plan before assisted reproductive treatment in 2017. A particular interest, in our case, submitted the special anamnesis including consideration of menstrual, sexual and reproductive functions, past gynecologic diseases and interventions.Results. In the analysis of the received results the most constant signs of chronic endometritis: disorders of menstrual and seсretory functions; the high index of intrauterine interventions, considerable frequency of identification of endometrium polyps and the cervical channel (40,1%), pathological cervical neoplasia (30,8%) were noted.Conclusion. Thus, anamnestic data of patients with the verified endometritis, especially extended one, with inclusion of nonconventional, but relevant at the present stage additional signs, have shown high informational content for neoadjuvant diagnosis of pathology of endometrium of inflammatory character. Only against the background of timely initiated complex therapy, numerous endometrial receptivity parameters are restored, which leads to relief of clinical symptoms and lays the foundation for the successful implementation of reproductive function.